The Technique of Prospecting and its Impact on the Constructionof Some Novels of "Ibrahim Nasrallah" - الشّـامي, حسّـان; أحمـد, لاريسّــا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The new novel tended to manipulate the time structure between anticipating/introducing and delaying the event, deleting and jumping, and other techniques or "time distortions" governed by laws, - as Tudrof called it – the effective use of which has contributed to the formation of the novel construction/structure. Experimentation in the narrative techniques of the time structure has destroyed the experience of time itself, in an attempt to reflect the fragmentary reality through a new narration, which raises questions, doubts and confusion at the reader’s side, and urges them to the foresight characters’ fates and the end of the events. The narrative techniques are usually defined according to narrative requirements, dictated by the nature of the constructional process, and the artistic vision of the writer, who has the ability to move among time levels, by playing with narration, and the chronological distortion of events. Novelists' methods of playing with novel time differed in a way to achieve their artistic goals. Novelist Ibrahim Nasrallah was one of many novelists who were interested in creating a coherent and profound time structure in their narrative work to monitor a reality characterized by cruelty and violence, undermining aspirations and dreams. This research deals with the technique of foresight / anticipation in selected narratives from the experience of the writer Ibrahim Nasrallah, showing its importance and impact on the time environment of the novel, and examines the style of the writer in the use of this time technique, and evoked in the formulation of his fiction.